2018
DOI: 10.1002/app.46345
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, analysis, and isothermal crystallization behavior of poly[1,3‐bis(aminomethyl)cyclohexamethylene oxamide]

Abstract: Poly[1,3-bis(aminomethyl)cyclohexaneoxamide] (PBAC2) was synthesized using 1,3-bis(aminomethyl)cyclohexane (BAC) and dibutyl oxalate (DO) via spray/solid-state polycondensation (SSP). The structure of the synthesized polyoxamide was confirmed by 1 H-nuclear magnetic resonance (NMR) and Fourier transform infrared spectroscopy. The weight average molecular weight (M w ) of the polyoxamides prepared was 1.35 3 10 5 . The polyoxamides showed excellent thermal properties with glass transition temperature (T g ) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The unique double hydrogen bonding endows it excellent performance, [22][23][24][25] such as high heat resistance, low water absorption, good crystallization properties together with mechanical properties. With the increasing demand for high temperature resistant polyamides in recent years, polyoxamides have aroused more and more attention in industry [26][27][28][29][30][31][32] and academia [33][34][35] and have a good marketing prospects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique double hydrogen bonding endows it excellent performance, [22][23][24][25] such as high heat resistance, low water absorption, good crystallization properties together with mechanical properties. With the increasing demand for high temperature resistant polyamides in recent years, polyoxamides have aroused more and more attention in industry [26][27][28][29][30][31][32] and academia [33][34][35] and have a good marketing prospects.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has further been reported that the relative insolubility of most polyoxamides prevents the formation of high molecular weight polymers when using conventional solution techniques. To obtain high molecular weight polyoxamides, a two stage procedure has been reported recently, [33][34][35] where a prepolymer is prepared at low temperature from a diester of oxalic acid and a diamine followed by solid state polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, polyoxamides with η int = 1.9 were prepared. Recently, much research on polyoxamides has been reported by utilizing this two‐step polymerization method, and high‐performance polyoxamides have been successfully synthesized 24–29 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, much research on polyoxamides has been reported by utilizing this two-step polymerization method, and high-performance polyoxamides have been successfully synthesized. [24][25][26][27][28][29] Comonomers are commonly utilized in polyamides to change the melt temperature and improve the processability. In this way, random copolyamides can be easily prepared.…”
mentioning
confidence: 99%